Risk Factors Of Pulmonary Respiratory Disorder Syndrome In Newborns - Ozoda A. Mirzabekova (Zien Journals, 2026)
In this article, the frequency and differences of risk factors for respiratory distress syndrome developing in the lungs of premature and full-term newborns were studied. As material, during the period 2017-2021, in the Department of Pediatric Pathology of the Republican Specialized Scientific and Practical Medical Center of Pediatric Anatomy, risk factors were studied according to the clinical and anamnestic analysis of the mother in cases of autopsy and detection of hyaline membrane in the lungs. The results showed that in most cases, asphyxia is a risk factor for the development of hyaline membranes in the lungs of premature infants - 74.5%, aspiration of amniotic fluid - 43.6%, and acute labor - 45.5%. As the main risk factor for the formation of hyaline membranes in the lungs of full-term newborns, the incidence of infection in the fetus during the prenatal period was 69.6%, and diabetes mellitus 59.3%. In full-term newborns, the following risk factors were identified: acute labor (43.7%), congenital heart defects (40.6%), pulmonary hypertension (34.3%).
Keywords: newborn; premature birth; full birth; lungs